Robots and Robotics Kits for Early Childhood and First School Age - Papadakis, Stamatios (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Educational robotics can consider one of the newest trends in education and they have been introduced into the classrooms ranging from kindergarten through high school as a means of enriching the learning environment and promote knowledge-building activities. Especially, robotics technologies offer opportunities for young age children, for a practical, hands-on understanding of the things they meet in their daily life but do not fully understand, such as proximity sensors, motion detectors, and light sensors, reasoning failures (software bugs) and connection problems (Wi-Fi, Bluetooth disconnection). In this article, we presented robots that can be used in early childhood and first primary classes of education. The purpose of this article is not to advocate against an educational robot or robotic kit but indeed to inform the educational community so that to make informed decisions regarding the introduction of this kind of technology into the classroom.